LEAF GAS EXCHANGE IN TWO DWARF COCONUT GENOTYPES IN THE SOUTHEAST OF BAHIA STATE, BRAZIL. - Gomes, F.P.; Mielke, M.S.; Almeida, A. F.; Muniz, W. S. (International Coconut Community, 2002)
Net photosynthetic (A) and leaf transpiration (E) rates and stomatal conductance to water vapour (gs) of Malayan Yellow Dwarf (MYD) and Brazilian Green Dwarf (BGD) coconut accessions (Cocos nucifera var. ‘nana’ L.) were studied and discussed in terms of the technical aspects related to light-response curves in field conditions. Measurements of gas exchange were performed during four days, in April and may 2000, at the Cocoa Research Center Experimental Station (Una - BA, Brazil). The A, gs and E parameters were significantly (P < 0.05) different between the two genotypes. The mean maximum values of A, gs and E were 10.4 and 12.0 µmol CO2 m-2 s-1, 0.21 and 0.35 mol H2O m-2 s-1 and 3.07 and 3.69 mmol m-2 s-1 for MYD and BGD, respectively. For both genotypes a good fitting of the light-response curve models were obtained, indicating that A and gs were dependent of the photosynthetically active radiation incident on leaf surface (Qi), in spite of high genotipic variation. Interesting results were achieved when an empirical multiplicative model was used. The model relating A or gs with Qi and with leaf-to-air water vapour pressure deficit inside the chamber (VPDL) was tested for both genotypes and showed a negative influence of the latter on the stomatal behavior and consequently on A. Such effect was more pronounced in BGD than in MYD. These and others relationships involving leaf gas exchange and microclimatic variables in coconut palm trees are discussed